2014
DOI: 10.1089/ham.2013.1112
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of High Altitude Pulmonary Hypertension Among the Natives of Spiti Valley—A High Altitude Region in Himachal Pradesh, India

Abstract: The study aimed to determine the prevalence of high altitude pulmonary hypertension (HAPH) and its predisposing factors among natives of Spiti Valley. A cross-sectional survey study was done on the permanent natives of Spiti Valley residing at an altitude of 3000 m to 4200 m. Demographic characteristics, health behavior, anthropometrics, and blood pressure were recorded. Investigations included recording of 12 lead electrocardiogram (ECG), SaO2 with pulse oximeter, spirometry and echocardiography study, and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
0
15
1
2
Order By: Relevance
“…Significant changes in blood coagulation at high altitudes may predispose individuals to pulmonary hypertension [25,26]. Negi et al [27] conducted a cross-sectional survey of permanent inhabitants in the Spiti Valley at an altitude of 3000 to 4200 m, although no significant correlation was found between altitude and pulmonary hypertension. However, it is still found that the prevalence rate is increasing with the increase of altitude; the data published to date have not been identified in plateau populations as genetic susceptibility to individual pulmonary hypertension [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Significant changes in blood coagulation at high altitudes may predispose individuals to pulmonary hypertension [25,26]. Negi et al [27] conducted a cross-sectional survey of permanent inhabitants in the Spiti Valley at an altitude of 3000 to 4200 m, although no significant correlation was found between altitude and pulmonary hypertension. However, it is still found that the prevalence rate is increasing with the increase of altitude; the data published to date have not been identified in plateau populations as genetic susceptibility to individual pulmonary hypertension [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, if the population resided at a higher altitude, a trend of higher risk of PH was observed. Therefore, different regions have different incidence and mortality rates . The average altitude in America is higher than that in Europe, and American populations had increased mortality compared to European populations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, based on current scientific literature we can assume that the rough prevalence of HAPH ranges from 5 to 18% in populations at risk and is more common in men. In a recent study by Negi et al demonstrated HAPH prevalence of 3.23% among natives of Spiti Valley, India [ 43 ].…”
Section: Epidemiology Of Haphmentioning
confidence: 99%